1990
DOI: 10.1029/ja095ia04p04307
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime equatorial thermospheric meridional winds from ionospheric h'F data

Abstract: Nighttime equatorial thermospheric meridional winds have been derived using h′F data from two equatorial stations nearly on the same magnetic meridian. It is shown that the winds derived are quite consistent with earlier observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…It may be mentioned that the postsunset height rise, observed using an equatorial ionosonde, does not involve the contribution due to meridional neutral winds [Krishna Murthy et al, 1990] and thus essentially represents the effect of the zonal electric field. To study the low-latitude E s parameters, we used ionosonde observations made from Sriharikota, a low-latitude station close to the Gadanki radar.…”
Section: Experiments and Data Analysis Methodologymentioning
confidence: 99%
“…It may be mentioned that the postsunset height rise, observed using an equatorial ionosonde, does not involve the contribution due to meridional neutral winds [Krishna Murthy et al, 1990] and thus essentially represents the effect of the zonal electric field. To study the low-latitude E s parameters, we used ionosonde observations made from Sriharikota, a low-latitude station close to the Gadanki radar.…”
Section: Experiments and Data Analysis Methodologymentioning
confidence: 99%
“…Further, to calculate wind velocities, the zero‐wind height or the layer peak height in the absence of plasma drift and transport has to be evaluated [ de Medeiros et al , 1997]. Krishna Murthy et al [1990] also derive meridional wind velocities from the time derivative of h′F obtained at magnetic equatorial and low latitude stations using standard atmospheric models to calculate the plasma diffusion drift term.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the nighttime meridional winds calculated by de Medeiros et al (1997) and that calculated by Krishnamurthy et al (1990) showed significant differences throughout the night, which may be attributed in part to the two widely different longitude sectors (Indian and Brazilian) and the epoch of study that their winds represented, among several other factors. Biondi et al (1999) have measured the thermospheric winds at Arequipa (Peru) and Arecibo (Puerto Rico) using Fabry-Perot interferometer technique applied to the 630 nm nightglow emission and they showed a large degree of night-to-night variation in the meridional wind that were attributed to the thermospheric circulation controlled by the solar EUV flux, latitude, longitude, subsolar point and local time variation.…”
Section: The Thermospheric Magnetic Meridional Windmentioning
confidence: 75%
“…Our analysis followed the methodology described by Krishnamurthy et al (1990) with some modifications introduced as will be explained eventually. The ionospheric data was obtained from the digisondes operated at São Luís and Fortaleza.…”
Section: The Thermospheric Magnetic Meridional Windmentioning
confidence: 99%
See 1 more Smart Citation